Analysis of Health-Seeking Behavior for Non-communicable Diseases: a Literature Review - Lu'lu Luthfiatun Ulinnuha; Titih Huriah (The Indonesian Institute of Science and Technology Research, 2025)
People's behavior in seeking health care is an important first step in preventing and controlling non-communicable diseases (NCDs). Non-communicable diseases account for 43 million deaths globally, with 82% of these premature deaths occurring in low- and middle-income countries. Therefore, this literature review aims to explore patterns of health-seeking behavior and the factors that influence them worldwide. This research employed a literature review method, with data searches conducted through Emerald Insight, PubMed, and Scopus, following the PRISMA protocol guidelines for literature reviews. The keywords used in the search strategy were